Theta power and theta‐gamma coupling support long‐term spatial memory retrieval. Issue 2 (2nd December 2020) - Vivekananda, Umesh; Bush, Daniel; Bisby, James A.; Baxendale, Sallie; Rodionov, Roman; Diehl, Beate; Chowdhury, Fahmida A.; McEvoy, Andrew W.; Miserocchi, Anna; Walker, Matthew C.; Burgess, Neil
Abstract: Hippocampal theta oscillations have been implicated in spatial memory function in both rodents and humans. What is less clear is how hippocampal theta interacts with higher frequency oscillations to support long‐term memory. Here we asked 10 presurgical epilepsy patients undergoing intracranial EEG recording to perform a long‐term spatial memory task in desktop virtual reality and found that increased theta power in two discrete bands ("low" 2‐5 Hz and "high" 6‐11 Hz) during cued retrieval was associated with improved task performance. Similarly, increased coupling between "low" theta phase and gamma amplitude during the same period was associated with improved task performance. Finally, low and high gamma amplitude appeared to peak at different phases of the theta cycle; providing a novel connection between human hippocampal function and rodent data. These results help to elucidate the role of theta oscillations and theta‐gamma phase‐amplitude coupling in human long‐term memory.